2019
DOI: 10.5812/ircmj.83291
|View full text |Cite
|
Sign up to set email alerts
|

The Family of People with Multiple Sclerosis: The Process of Family Stress Adaptation

Abstract: Background: Multiple Sclerosis (MS) affects everyday functioning of individuals with MS, and their family dynamics. Furthermore, MS is a chronic disease with unpredictable course imposing a stressful experience on the entire family. Changes in family functioning patterns are necessary so that they can appropriately respond to complex demands imposed by the disease. Objectives: This study aimed to evaluate predictive values of family resources in the encounter with stressful life events and family adaptation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…To reduce family stress and improve family adaptation, family resilience is important [ 44 ], given that resilience is a protective factor for family [ 45 ]. Our study showed that family stress had a negative effect on family adaptation, which is consistent with previous studies on the families of patients with chronic illnesses [ 18 , 46 , 47 ]. Thus, when nurses provide nursing care to patients with brain tumors in the clinical field, they should consider what kinds of stress the families of patient experience and find various interventions to relieve their stress.…”
Section: Discussionsupporting
confidence: 92%
“…To reduce family stress and improve family adaptation, family resilience is important [ 44 ], given that resilience is a protective factor for family [ 45 ]. Our study showed that family stress had a negative effect on family adaptation, which is consistent with previous studies on the families of patients with chronic illnesses [ 18 , 46 , 47 ]. Thus, when nurses provide nursing care to patients with brain tumors in the clinical field, they should consider what kinds of stress the families of patient experience and find various interventions to relieve their stress.…”
Section: Discussionsupporting
confidence: 92%
“…Based on the experiences of our participants, the family's appropriate behavior is effective in and facilitates the patient's adjustment. Brkić-Jovanović et al (2019) argued that the main factor contributing to adjustment to this disease lies within the family; therefore, adjustment can be improved by strengthening support and communication in the family. Khanjani et al (2019) also argued that receiving the right support from the family along with the delegation of responsibility to the patient and accompanying and empathizing with them contribute to the patient's acceptance and adjustment to the disease conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The high perceived social support in dependent patients for ADL with a long diagnosis period can be explained by the demanding care of the patient in the face of increasing patient needs and the adaptation and modification of the care content that family members should offer according to new needs. In the study conducted by Brkić‐Jovanović et al, 76 it was stated that the most important determinants affecting the harmony of MS patients with their family and the quality of their intra‐family relationships were the quality of communication and social support within the family. It was observed that social support received from any source other than the family had no statistically significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that social support received from any source other than the family had no statistically significant effect. Social support, especially received from family members within the nuclear family, ensures the quality of intrafamily communication 76 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation